Å forebygge ulvedrap - Paul Larsson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article deals with the prevention of the illegal hunting of wolves in Norway and is based on research conducted between 2016 and 2019. The main actors are the local police and the rangers / guards of the Norwegian Environmental Protection Agency (NEPA). Resources used on wildlife crimes by the local police are limited. Most of the surveillance of poaching is done by NEPA guards. Strategies for preventing poaching have not been well-developed. Prevention is incorporated in the routine daily activities of the guards. General surveillance is a central element. Much of what has been done can be labelled situational crime prevention and there are elements of routine activities theory reflected in the practice. There are hot spots (locations of wolf packs) that are patrolled at times of heightened risk (January through March). Police and the rangers often patrol these areas in uniformed cars and use other ways of signalling their appearance. Information and dialog with locals and hunters are important elements of the preventive effort. Since wildlife crime is linked to open conflicts between locals, but also to conflicts between locals and  representatives for the central authorities, there have been attempts at conflict resolution and mediation. Knowledge concerning the effects of these measures is limited since there have been no follow-up evaluations of these activities.